Polyurethane Application to Transform Screen-Printed Electrode for Rapid Identification of Histamine Isolated from Fish - Muhammad Abdurrahman, Munir; Jamia Azdina, Jamal; Mazlina, Mohd Said; Sofan, Ibrahim; Mohamad Syahrizal, Ahmad (Hindawi Publishing, 2023)
The toxicity of histamine has attracted numerous researchers to develop a method for histamine determination purposes. The Food and Drug Administration (FDA) unequivocally prohibits the consumption of histamine above 50 mg·kg−1. Thus, an innovation in histamine detection in fish has been developed in this research. The investigation of the histamine level in fish has been conducted by using an electrochemical sensor approach and producing a polymer via molecularly imprinted polymer (MIP) on a screen-printed electrode. The technique was validated by assessing the shifts in electron shifting using the cyclic voltammetry (CV) approach and electrochemical impedance spectroscopy (EIS), whereas differential pulse voltammetry (DPV) was applied to validate the sensor method. The instruments showed a linear response ranging from 1–1000 nmol·L−1, with a detection limit of MIP/SPE at 1.765 nmol·L−1 and 709 nmol·L−1 for the NIP/SPE, respectively. The sensing technique was employed to determine the histamine level in selected samples at room temperature (25°C). The outcomes of this study indicated that the validated chemical sensor allowed accurate and precise detection of fish samples and can be categorized as a simple approach. The instrument is inexpensive and suitable for on-site detection.